Fractional Er:YAG skin conditioning for enhanced efficacy of Nd:YAG Q-switched laser tattoo removal - Marini, Leonardo (LAHA (Online ed.), 2012)
In this study a new approach to laser tattoo removal is proposed. Although Q-switched laser systems have become the gold standard in tattoo removal, they also have their limitations. To overcome existing procedure limits, pre-treatment conditioning of the skin with a fractional Er:YAG laser was studied. Laser-drilled micro channels known as skin perforations were found to enhance the efficacy of the laser tattoo-removal process, while reducing the healing time and enabling effective multiple treatments during each session.
Keywords: Er:YAG laser fractional treatment; laserji; lasers; odstranjevanje tetovaž; optoakustični pojav; optodinamika; optodynamic; photoacoustic effect; Q-switched lasers; tattoo removal